THE MASTER OF SCIENCE IN EDUCATION A WAY TO IMPROVE THE PROFESSIONAL TEACHING PERFORMANCE OF TEACHERS OF TECHNICAL AND PROFESSIONAL EDUCATION IN THE PROVINCE OF MATANZAS - Hernández Fuentes , Marisel; Santos Muñoz, Noraida (Atenas, 2012)
The Master of Science in Education is an Education Revolution in Cuba, since through it has been the improvement of all processes occurring at different levels of education to which belong the maestrantes. The peculiarities, the main achievements and its impacts within the Master of Science in Education, Minor in Technical and Vocational Education in the province of Matanzas and mainly the impact it has had on the performance of teachers teaching stand out in this work and the remaining gaps are and where we need to continue working.